2011
DOI: 10.1074/mcp.m111.009100
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycans Modulate the Function of Human Corticosteroid-Binding Globulin

Abstract: Human corticosteroid-binding globulin (CBG), a heavily glycosylated protein containing six N-linked glycosylation sites, transports cortisol and other corticosteroids in blood circulation. Here, we investigate the biological importance of the N-glycans of CBG derived from human serum by performing a structural and functional characterization of CBG N-glycosylation. Liquid chromatography-tandem MS-based glycoproteomics and glycomics combined with exoglycosidase treatment revealed 26 complex type N-glycoforms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 51 publications
2
86
1
Order By: Relevance
“…However, even the definition of this threshold is an analytical artefact, as it is increasingly apparent that most glycosylated Asn are only partially modified, with some portion ranging from a fraction of a percent to essentially all copies of a protein, actually glycosylated (Hülsmeier et al, 2007, Sumer-Bayraktar et al, 2011. This pattern seems to contrast with the general requirement of many proteins for Nglycosylation for correct and efficient protein folding (Helenius & Aebi, 2004).…”
Section: The Future Of the Sequonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even the definition of this threshold is an analytical artefact, as it is increasingly apparent that most glycosylated Asn are only partially modified, with some portion ranging from a fraction of a percent to essentially all copies of a protein, actually glycosylated (Hülsmeier et al, 2007, Sumer-Bayraktar et al, 2011. This pattern seems to contrast with the general requirement of many proteins for Nglycosylation for correct and efficient protein folding (Helenius & Aebi, 2004).…”
Section: The Future Of the Sequonmentioning
confidence: 99%
“…However, as glycosylation generally results in a complex mixture of glycan structures at each glycosylation site, measurement of the abundance of the glycosylated form of a given site is not trivial. Some approaches have used detection of entire glycopeptides, although this approach generally requires more specialized and targeted LC-MS technologies (Sumer-Bayraktar et al, 2011). Other approaches have focused on improving quantification of occupancy, and have discarded information on site-specific glycan structure by endoglycosidase treatment ).…”
Section: Mass Spectrometry For Measuring Glycosylation Occupancymentioning
confidence: 99%
“…This has led some to speculate that CBG may act as a hormone and there may be a direct contribution of bound cortisol in glucocorticoid bioavailability via this yet unidentified CBG receptor 34 . Accumulation of cyclic AMP 35 occurs as a result of this CBG:cell receptor interaction. Recently, it has been shown that the NeuAc residues on the N-glycans restrict the binding of CBG to the cell receptor.…”
Section: Corticosteroid-binding Globulin: More Than Just a Transport mentioning
confidence: 99%
“…Recently, it has been shown that the NeuAc residues on the N-glycans restrict the binding of CBG to the cell receptor. Removing these NeuAc residues resulted in marked increase in cyclic AMP levels 35 . Dilution of CBG results in release of cortisol and thus suggests, at the very least, an indirect contribution of bound cortisol in glucocorticoid bioavailability 36 .…”
Section: Corticosteroid-binding Globulin: More Than Just a Transport mentioning
confidence: 99%
“…For example, human corticosteroid-binding globulin, a major plasma glycoprotein with six N-glycosites, has variable degrees in occupancy among its six glycosites (ranging from 70 to 99.5%) that also seem to change with pregnancy (16). Although the biological implications of partial occupancy in N-glycosylation are not well understood, to date, there are no well-defined strategies that can readily identify PO glycosites, particularly in a complex mixture.…”
mentioning
confidence: 99%